Intersections of family homelessness, CPS involvement, and race in Alameda County, California. (July 2016) - Rodriguez, Jason M.; Shinn, Marybeth
Abstract: The homelessness and child protective services (CPS) systems are closely linked. This study examines the patterns and sequence of families' involvement with homeless shelters and CPS, as well as whether involvement in each system predicts involvement in the other using linked administrative records for 258 families recruited in emergency shelters in Alameda County, California. More than half of families were reported to CPS at some point, but less than one-fifth ever had a report substantiated. Reports that were uninvestigated or unfounded increased in the months leading up to shelter entry and spiked immediately afterward, but substantiations and child removals increased only later. Shelter use before study entry was associated with CPS referrals and investigations after study entry, although not with substantiated cases or child removals. However, CPS involvement before study entry was not associated with returns to shelter after study entry. These results imply that an unsubstantiated report of neglect or abuse may serve as an early warning signal for homelessness and that preventive strategies aiming to affect both homeless and child protective systems should focus on reducing homelessness. CPS workers should evaluate families' housing needs and attempt to link families to appropriate resources. Black families were disproportionately referred to CPS after shelter entry after controlling for other family characteristics, but race was not associated with substantiations of neglect or abuse or with child removals. Findings lend modest support to human decision-making and institutional explanations of racial disproportionalities in CPS involvement, especially for reporters outside of the CPS system.